Relación de anemia ferropénica y caries en la primera infancia en niños atendidos en la IPRESS I-4 San Juan-2025 - Gonzales Tello, Juana Rosa Lucía (2025)
This study aimed to analyze the relationship between iron-deficiency anemia and the severity of early childhood caries in children treated at the Primary Health Care Facility (IPRESS) I-4 “San Juan” during 2025. It was a quantitative, descriptive, cross-sectional study with a correlational design, conducted on a sample of 169 children under six years of age. Simple random probability sampling was used and the techniques used included reviewing the CRED service care books to obtain the children's hemoglobin levels and performing clinical dental evaluation. The collected data were coded and processed in a database using SPSS software, version 27.0. Pearson’s Chi square test (χ²) was applied for inferential analysis, with a significance level of p <0,05. Results showed that most children were 4 years old (43,8%), with a mean age of 4.1 ± 0,7 years, and a predominance of males (54,4%). A high prevalence of iron-deficiency anemia was observed, with mild (51,5%) and moderate (34,9%) forms being the most common, and an average hemoglobin level of 9.9 ± 0,8 g/dL. Regarding early childhood caries, the mean ceo-d index was 1,6 ± 0,9, with the low-severity category predominating (49,1%). No statistically significant association was found between hemoglobin levels and caries severity (p=0,767), nor was there a relevant linear correlation between these variables (ρ=-0,028; p=0,718). In conclusion, a high prevalence of irondeficiency anemia was identified in the studied pediatric population; however, no significant relationship was established with the presence or severity of early childhood caries.